The Effect of Organizational Commitment and Work Discipline on Job Satisfaction - Donny Dharmawan; M. Anwar; Isniar Budiarti; Indah Lestari; Santi Nururly (International Journal of Economics Development Research (IJEDR), 2023)
The aim of this research is to investigate the potential correlation between organizational commitment and work discipline with employee job satisfaction. The study involves 110 employees from both general and personnel divisions, comprising the research population. Saturated sampling, also known as census sampling, is utilized in this study. The data analysis method employed is path analysis, preceded by confirmatory factor analysis to validate the indicators representing the variables or constructs. The results of path analysis shed light on the impact of discipline and organizational commitment on job satisfaction. The study confirms the theoretical notion that individuals tend to experience higher levels of satisfaction when they exhibit greater dedication, provided that discipline is maintained. The practical implications of this research are intended to guide decision-making and policy formulation regarding discipline, organizational commitment, and job satisfaction within PT Mustika Ratu.